DETERMINAN KINERJA KADER POSYANDU DALAM PEMANTAUAN TUMBUH KEMBANG BALITA DI PUSKESMAS JURUMUDI BARU KOTA TANGERANG TAHUN 2021 - Maharanti (2022)
The COVID-19 pandemic caused a decrease in the coverage of active posyandu in Tangerang City in 2020 which had an impact on the coverage of active posyandu in Indonesia it was deemed necessary to be a concern. To increase this coverage again, it is very necessary to have an active role from local posyandu cadres. This study aims determinant factor of posyandu cadres performance in monitoring the growth and development of toddlers at the Jurumudi Baru Health Center in Tangerang City with the instrument used a questionnaire. This research used quantitative research with a cross-sectional design and sampling technique in this study used purposive sampling technique with the samples of 137 posyandu cadres. The analysis used is chi-square and multiple logistic regression. The results of the bivariate analysis showed that there was a relationship between individual factors (age, length of work, and knowledge), psychological factors (cadres attitudes), and organizational factors (training, incentives and posyandu facilities) with the performance of cadres in monitoring the growth and development of toddlers. The results of the multivariate analysis showed that the cadre incentive variables (p=0.000; POR=11,831), posyandu facilities (p=0.001; POR=7,682), training (p=0.009; POR=4.561) and cadre age (p=0.048; POR= 2.831) entered into the multivariate final model. Cadre incentives are the most influential factor on the performance of cadres in monitoring the growth and development of toddlers. The public health center is expected to continued to evaluate and monitor the performance of cadres and maximize the provision of motivation for cadres in the form of incentives, assistance and training on a regular and ongoing basis. Keywords: Factors, Cadres Performance, and Monitoring of Toddler Growth